Application of the microwave field in jelly products technology - Andriy Foshchan (Technology Audit and Production Reserves, 2021)
The object of research is the agar-based chocolate-jelly cake technology. Due to the annual decrease in the production of natural jelly-forming agents and their high price, the possibilities of improving the qualitative change in their functional properties are being studied. In this connection, various methods of modification by gelling agents, both chemical and physical, are proposed.